Application of multistage artificial immune system for solving unit commitment / Nazlan Azizi Abd Aziz - Abd Aziz, Nazlan Azizi (2009)
This paper presents a new approach to develop a multistage of artificial immune system (AIS) method for solving the unit commitment using suitable method programming. The objective is to find the generating scheduling such that the total operating cost can be minimized, when subjected to the range of a set of constraints. This means that it is needed to find the optimal generating unit commitment in the power system for each of twenty four hours. The AIS is an optimization technique for solving unit commitment problem, operates on a system, which is designed to encode each unit's operating schedule based on its minimum up/down time. An initial population of first solution is generated at random. Each schedule is formed here by committing all of the units according to their initial status. Here, the first solution are obtained from a predefined set of solutions (i.e., each and every solution is adjusted to meet the requirements). Then a random recommitment is carried out with respect to the unit's minimum downtimes. The initial population will be clone in the first of AIS step which is known as a clonal selection process. Then selected generating units are subject to an affinity mutation process, which improves their affinity to the selective population. Numerical results are shown the comparison between the total costs of both single and multistage obtained by using the AIS method.